2003
DOI: 10.1063/1.1536729
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved electroluminescence of AlGaN-based light-emitting diodes with emission at 285 nm

Abstract: We present a study on the time evolution of the electroluminescence (EL) spectra of AlGaN-based deep ultraviolet light-emitting diodes (LEDs) under pulsed current pumping. The EL spectra peaks at 285 nm and 330 nm are found to result from recombination involving band-to-band and free carriers to deep acceptor level transitions. The 330 nm long-wavelength transitions to deep acceptor levels in the p-AlGaN layer as well as the nonradiative processes significantly influence the LED internal quantum efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 13 publications
3
39
0
Order By: Relevance
“…For the 285 nm emission, we previously reported room-temperature power as high as 0.25 mW for a pulsed pump current of 650 mA. 9 These studies 8,9 also concluded that the emission band at 330 nm resulted from a recombination of the electrons via deep neutral acceptor levels in the p-AlGaN layer of our device structure. The data suggested that the weak carrier confinement not only results in a long-wavelength emission ͑at 330 nm͒, but it also reduces the 285 nm emitted powers.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…For the 285 nm emission, we previously reported room-temperature power as high as 0.25 mW for a pulsed pump current of 650 mA. 9 These studies 8,9 also concluded that the emission band at 330 nm resulted from a recombination of the electrons via deep neutral acceptor levels in the p-AlGaN layer of our device structure. The data suggested that the weak carrier confinement not only results in a long-wavelength emission ͑at 330 nm͒, but it also reduces the 285 nm emitted powers.…”
mentioning
confidence: 82%
“…7,8 At higher currents it rapidly saturates with a simultaneous increase in the 285 nm peak, which then dominates the spectra at pump currents in excess of 200 mA. For the 285 nm emission, we previously reported room-temperature power as high as 0.25 mW for a pulsed pump current of 650 mA.…”
mentioning
confidence: 99%
“…A feature at 320 nm has been observed in 285 nm 25) and 292 nm LEDs 5) based on Al x Ga 1Àx N alloys. It was attributed to a free-carrier to deep acceptor transition in Mg-doped pAl 0:4 Ga 0:6 N. 5,25) Such a transition could arise in our DASbased LED because of the formation of 1 ML thick barrier/ well interfaces in which the AlN concentration may vary.…”
Section: Optical and Electrical Measurementsmentioning
confidence: 97%
“…It was attributed to a free-carrier to deep acceptor transition in Mg-doped pAl 0:4 Ga 0:6 N. 5,25) Such a transition could arise in our DASbased LED because of the formation of 1 ML thick barrier/ well interfaces in which the AlN concentration may vary. The total volume fraction of these regions throughout the DAS can be considerable since the period is small, i.e., it scales like ÁL=L, where ÁL is the effect of monolayer fluctuations and L is the period.…”
Section: Optical and Electrical Measurementsmentioning
confidence: 99%
“…An additional emission in the wavelength range of 350 nm to 550 nm can be observed. The latter is generated by deep level emission associated with Mg acceptors or other impurities and defects [6,7]. The SQW LED spectrum shows two shoulders beside the main peak which are most likely due to carrier recombination in the n-type AlGaN and the p-type AlGaN/GaN superlattice.…”
Section: Methodsmentioning
confidence: 97%